PROOF OF MATHEMATICAL FORMULAS USING THE METHOD OF MATHEMATICAL INDUCTION - Sobirova Dinora Umidjon qizi (TADQIQOTLAR, 2025)
Abstract: Mathematical induction is a fundamental method of proof in mathematics, particularly useful in establishing the validity of formulas and statements involving natural numbers. This article explores the principles and logical structure of mathematical induction through carefully selected examples and step-by-step analyses. By applying this method to various arithmetic and algebraic formulas, the study demonstrates how induction provides a clear and rigorous approach to proof construction.